Numerical simulation of large wood deposition patterns and responses of bed morphology in a braided river using large wood dynamics model. Issue 4 (2nd January 2020) - Kang, Taeun; Kimura, Ichiro; Shimizu, Yasuyuki
Abstract: This study discusses the reproducibility of a numerical model for simulating the morphodynamics involved in the transport of large pieces of wood in a braided river, considering the root wad effect and jam formation. The developed numerical model can simulate the behaviour of large pieces of wood using a two‐dimensional depth‐averaged Eulerian flow model that calculates the water flow and bed morphology. A Lagrange‐type wood transport model is used herein, and the applicability of the combined model is discussed through a comparison with obtained experimental results. From the simulation results, we calculate the total braiding index and estimate the deposition patterns of wood pieces for comparison with the experimental results. We then analyse the bed morphology responses and wood deposition patterns in terms of the root wad effect and input supply. Moreover, we discuss the advantages and limitations of the proposed model to predict the large wood dynamics considering the bed morphology. © 2019 John Wiley & Sons, Ltd. Abstract : This study discusses the reproducibility of a numerical model for simulating the morphodynamics involved in the transport of large pieces of wood in a braided river.